Effect of fluvoxamine on plasma interleukin-6 in patients with major depressive disorder: a prospective follow-up study - Li, Xueqin; Yan, Danfeng; Liao, Mei; Zhang, Li; Li, ZeXuan; Liu, Bangshan; Chen, Yanjun; Zhang, Yan; Liu, Jin; Li, LingJiang (Frontiers in Psychiatry, 2023)
Introduction Major depressive disorder (MDD) is associated with low-grade inflammation, and anti-inflammatory treatment can help improve depressive symptoms. A recent study found that fluvoxamine (FLV) can reduce Interleukin-6 (IL-6) production via sigma-1 receptor in inflammation models. However, the anti- IL-6 effect of FLV in treating patients with MDD and whether it can contribute to antidepressant effects remain unclear. Methods A total of 65 patients with MDD and 34 healthy controls were recruited at baseline, and 50 patients completed the FLV treatment for 2 months. We assessed depression and anhedonia and collected plasma IL-6 levels at baseline, 1 month, and 2 months after baseline. This study evaluated the changes in clinical measures and IL-6 during treatment and analyzed their association. Further subgroup analyses were conducted in patients with MDD with high, medium, or low IL-6. Results Depression and anhedonia were significantly improved in patients with MDD, while the IL-6 did not significantly change after the FLV treatment. However, IL-6 significantly declined after the FLV treatment among patients with MDD with higher baseline IL-6. No significant associations were found between the changes in depressive symptoms and IL-6. Conclusion Our study provided preliminary evidence suggesting that the anti-IL-6 effect of FLV might not play a vital role in its antidepressant treatment, at least in patients with MDD with low inflammation. However, for patients with MDD with higher IL-6, FLV can help reduce IL-6 significantly in the antidepressant treatment, which may help guide the individual treatment of MDD with higher IL-6 levels. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT04160377, identifier NCT04160377.